Calles - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: Foto antigua del Malecón Tarapaca con la esquina de la primera cuadra de Brasil
ENGLISH: Old photo of the Malecón Tarapaca with the corner of the first block of Brasil.

SPANISH: Foto antigua del Malecón Tarapaca con la esquina de la primera cuadra de Brasil
ENGLISH: Old photo of the Malecón Tarapaca with the corner of the first block of Brasil.
Streets
Keywords: Iquitos (Perú)|~|Streets|~|Calles|~|Iquitos (Perú)